Negative Impact of Online Loans on Muslim Family Harmonization in Kediri District West Lombok - Muhammad Asroruddin; Sainun, Sainun; Lalu Muhammad Nurul Wathani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Economic stability is the main pillar in building a sakinah family. In this regard, economic stability in today's society is affected by online loans. The risks caused by online lending affect the psychological, social, and even emotional conditions in household life, and can further affect household harmony. This research will explore the form of online lending practices and analyze the impact of online lending on household harmony in West Lombok Regency. The research was conducted using a qualitative method. The results of the research found First: Layered Motivation signifies that Muslim families resort to online loans as a result of a mix of urgent circumstances, economic strain, insufficient literacy, and restricted access to conventional banking. Second: Multidimensional Impact suggests that online loans not only harm the economy but also dismantle the social, psychological, and spiritual structures of Muslim families. Third: Destructive Cycle demonstrates that online loans establish a vicious cycle where financial remedies worsen issues and undermine family unity. Fourth: Crisis of Religious Identity emphasizes that engagement in usury generates spiritual discord and jeopardizes the passing down of Islamic values to subsequent generations. Fifth: Systemic Vulnerability indicates that rural populations are at risk of online loan exploitation due to inadequate digital financial literacy and limited availability of Sharia-compliant financial services.